Newborn Weight Loss as a Predictor of Persistence of Exclusive Breastfeeding up to 6 Months - Delfino, Enrica; Peano, Luca; Wetzl, Roberto Giorgio; Giannì, Maria Lorella; Netto, Roberta; Consales, Alessandra; Bettinelli, Maria Enrica; Morniroli, Daniela; Vielmi, Francesca; Mosca, Fabio; Montagnani, Luca (Frontiers in Pediatrics, 2022)
Objectives To investigate the association between neonatal weight loss and persistence of exclusive breastfeeding up to six months. Study design An observational cohort study in the setting of a Baby Friendly Hospital, enrolling 1260 healthy term dyads. Neonatal percentage of weight loss was collected between 48 and 72 hours from birth. Using a questionnaire, all mothers were asked on the phone what the infant’s mode of feeding at ten days, 42 days and six months (≥183 days) from birth was. The persistence of exclusive breastfeeding up to six months and the occurrence of each event that led to the interruption of exclusive breastfeeding were verified through a logistic analysis that included 40 confounders. Results Infants with a weight loss ≥7% were exclusively breastfed at six months in a significantly lower percentage of cases than infants with a weight loss <7% (95% CI 0.563 to 0.734, P<.001). Weight loss ≥7% significantly increases the occurrence of either sporadic integration with formula milk (95% CI 0.589 to 0.836, P<.001), complementary feeding (95% CI 0.460 to 0.713, P<.001), exclusive formula feeding (95% CI 0.587 to 0.967, P<.001) or weaning (95% CI 0.692 to 0.912, P=0.02) through the first six months of life. Conclusions With the limitations of a single-centre study, a weight loss ≥7% in the first 72 hours after birth appears to be a predictor of an early interruption of exclusive breastfeeding before the recommended six months in healthy term exclusively breastfed newborns.